1978
DOI: 10.2307/412789
|View full text |Cite
|
Sign up to set email alerts
|

The Linguistic Significance of the Meanings of Basic Color Terms

Abstract: Sample entries:hotamti vi. p.pl. get stretched out.-Itupko kaway 'uyit hotamtiqw tiikive'ytani, When the watermelons stretch (with vines on the ground), my younger brother will sponsor a dance. paapu part.[2] from now on, from this time on.-Nu' teevep taya 'iwtaqw nungwupaapu ipono hin 'ur tuyva, F ve been laughing so long my stomach is now starting to hurt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
212
0
12

Year Published

1983
1983
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(230 citation statements)
references
References 0 publications
6
212
0
12
Order By: Relevance
“…Neurophysiological explanations tie the Basic Colours to the form of the cone spectral-sensitivity functions (Griffin, 2001;Buchsbaum and Bloch, 2002), to some later processing stage such as opponent channels (Kay and McDaniel, 1978;DeValois et al, 1966;Hering, 1920;Hurvich and Jameson, 1957;Kay and Maffi, 1999) or to dedicated neural mechanisms (Steels and Belpaeme, 2005). Neurophysiology may also limit what categories are possible, for example we may lack cognitive structures capable of representing disconnected or non-convex regions of colour space (Gärdenfors, 2000).…”
Section: Featuresmentioning
confidence: 97%
“…Neurophysiological explanations tie the Basic Colours to the form of the cone spectral-sensitivity functions (Griffin, 2001;Buchsbaum and Bloch, 2002), to some later processing stage such as opponent channels (Kay and McDaniel, 1978;DeValois et al, 1966;Hering, 1920;Hurvich and Jameson, 1957;Kay and Maffi, 1999) or to dedicated neural mechanisms (Steels and Belpaeme, 2005). Neurophysiology may also limit what categories are possible, for example we may lack cognitive structures capable of representing disconnected or non-convex regions of colour space (Gärdenfors, 2000).…”
Section: Featuresmentioning
confidence: 97%
“…(De Valois et al 1966;De Valois and De Valois 1975.) The physiological primacy of four (or six, including also white and black 1 ) unique hues was subsequently adopted as a powerful explanatory principle R. Ocelák (&) Institute of Philosophy and Religious Studies, Charles University in Prague -Faculty of Arts, náměstí Jana Palacha 2, 116 38 Prague 1, Czech Republic e-mail: radioc@seznam.cz in color categorization (or color naming) research (Hardin 1988; Kay and McDaniel 1978; in a more restrained form Kay and Maffi 1999;and even Kay et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The universal view has, at least until recently, become the established position in the field with the implication that there are innate physiological mechanisms underlying color categories. In support of the universalist view, Kay and McDaniel (1978) suggested that primary categories (red, green, yellow and blue) derive from the output of opponent-process cells. These cells selectively respond to different ranges of wavelength, and produce the well-known phenomenon of colored after-images.…”
mentioning
confidence: 99%